Loss or oncogenic mutation of DROSHA impairs kidney development and function, but is not sufficient for Wilms tumor formation. Issue 6 (3rd December 2018) - Kruber, Philip; Angay, Oguzhan; Winkler, Anja; Bösl, Michael R.; Kneitz, Susanne; Heinze, Katrin G.; Gessler, Manfred
Abstract : Wilms tumor (WT) is the most common kidney cancer in childhood. Mutations in the microprocessor genes DROSHA and DGCR8 have been identified as putative oncogenic drivers, indicating a critical role of aberrant miRNA processing in WT formation. To characterize the in vivo role of DROSHA mutations during kidney development and their oncogenic potential, we analyzed mouse lines with either a targeted deletion of Drosha or an inducible expression of human DROSHA carrying a tumor‐specific E1147K mutation that acts in a dominant negative manner. Both types of mutation induce striking changes in miRNA patterns. Six2‐cre mediated deletion of Drosha in nephron progenitors led to perinatal lethality with apoptotic loss of progenitor cells and early termination of nephrogenesis. Mosaic deletions via Wt1‐cre ERT2 resulted in a milder phenotype with viable offspring that developed proteinuria after 2–4 weeks, but no evidence of tumor formation. Activation of the DROSHA ‐ E1147K transgene via Six2‐cre, on the other hand, induced a more severe phenotype with apoptosis of progenitor cells, proteinuria and glomerular sclerosis. The severely growth retarded mice died within the first 2 months of life, confirming the predicted dominant‐negative effect of DROSHA‐E1147K in vivo . While our data underscores the importance of a viable self‐renewing progenitor pool for kidney development, there was no evidence of tumor formation through impaired DROSHA function. This suggests that either additional alterations in mitogenic or antiapoptotic pathways are needed for malignant transformation, or premature loss of a susceptible target cell population and early lethality prevent WT formation. Abstract : What's new? Mutations in microprocessor genes including DROSHA have been identified as putative oncogenic drivers in Wilms tumor (WT), the most common childhood kidney cancer. our study sheds light on the role of DROSHA mutations during kidney development and their oncogenic potential using a mouse model. The data show that oncogenic DROSHA mutations seen in Wilms tumors are dominant‐negative alterations in vivo that strongly impair kidney development through loss of progenitor cells, impaired differentiation, and early lethality. Yet, the mutations alone appear insufficient to induce tumor formation, and additional genetic alterations may be needed to fully recapitulate WT formation in the mouse.